2015
DOI: 10.1159/000369387
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Adenosquamous Carcinoma and Adenocarcinoma of the Cervix after Radical Hysterectomy

Abstract: Background/Aims: The aim of this study was to compare the survival outcomes of adenocarcinoma and adenosquamous carcinoma in early-stage cervical cancer patients after radical hysterectomy. Methods: A retrospective analysis was performed of stage IB-IIA cervical cancer patients with adenocarcinoma or adenosquamous carcinoma who underwent radical hysterectomy at Seoul National University Hospital between 1998 and 2008. Results: A total of 166 patients with adenosquamous carcinoma (ASC) (n = 38) and adenocarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, the newest analysis by Lee et al [13] showed comparable survival outcome between histology of AS and ASC in patients with stage IB-IIA cervical cancer receiving radical surgery although the ASC group presented more poor pathologic findings. Hong et al [12] also reported their experience of 928 patients with cervical cancer FIGO stage I-IVB who received radiotherapy as the initial treatment, and the patients with AC/ASC had a significantly higher residual disease rate after radiotherapy (40 vs. 21.6%), higher local failure rate (38 vs. 15%) and lower 5-year DFS (50 vs. 66%) compared to patients with SCC [13]. Because the patients in these studies received radiotherapy as a part of their treatment, the underlying radio-responsiveness of AC or ASC may have contributed to the treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the newest analysis by Lee et al [13] showed comparable survival outcome between histology of AS and ASC in patients with stage IB-IIA cervical cancer receiving radical surgery although the ASC group presented more poor pathologic findings. Hong et al [12] also reported their experience of 928 patients with cervical cancer FIGO stage I-IVB who received radiotherapy as the initial treatment, and the patients with AC/ASC had a significantly higher residual disease rate after radiotherapy (40 vs. 21.6%), higher local failure rate (38 vs. 15%) and lower 5-year DFS (50 vs. 66%) compared to patients with SCC [13]. Because the patients in these studies received radiotherapy as a part of their treatment, the underlying radio-responsiveness of AC or ASC may have contributed to the treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, high-risk histologies, such as neuroendocrine and serous tumors of the cervix, have poor prognosis than squamous cell carcinoma and adenocarcinoma [17]. Meanwhile, Lee et al [18] reported that there was no significant difference in survival outcomes between adenocarcinoma and adenosquamous carcinoma in early-stage cervical cancer patient after radical hysterectomy. Some patients with neuroendocrine tumors have distant metastasis, despite radical hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Peter et al reported that adenocarcinoma and ASC of the cervix are associated with worse OS when treated with radiation alone, but have similar progression free and overall survival compared to squamous cell carcinomas of the cervix when treated with cisplatin-based chemoradiation [ 24 ]. Lee et al concluded that intermediate/high-risk patients with ASC may be successfully treated with postoperative CCRT [ 25 ]. In both studies, ASC was compared to squamous and adenocarcinoma rather than to itself, which may lead to bias.…”
Section: Discussionmentioning
confidence: 99%